Comparação entre o comportamento enxuto de engenheiros do setor público e do setor privado - Silva, Jorge Luis Oliveira; Cruz, Herbert Melo; Santos, Débora de Gois (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
The aim of the research was to compare lean behavior among engineers working in public sector with engineers working in private sector. The method consisted in applying a questionnaire with the engineers working in public or private sector. The questions were divided in to the groups: definition of work, measurement of work, communication and dissemination of information, guidance and motivation of workers, work scheduling, use of equipment and productive chain. For the application of this questionnaire, 15 engineers from the state of Bahia and Sergipe were selected. As a result, it was observed in the research that there is a lean behavior on the part of the public and private engineers. However, there is also a greater difficulty by engineers (tax) in relation to the use of the lean principles. It was also evidenced that labor measurement is a recurring problem in the public and private sectors.